A IMPLEMENTATION OF NATIONAL INDICATORS FOR QUALITY OF HEALTH CARE SERVICES IN PUBLIC HEALTH CENTER IN WEST JAVA PROVINCE: IMPLEMENTATION OF NATIONAL INDICATORS FOR QUALITY OF HEALTH CARE SERVICES IN PUBLIC HEALTH CENTER IN WEST JAVA PROVINCE - Tanti Oktriani, Dewi Purnamawati (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
The National Quality Indicator (INM) is one of the benchmarks in efforts to improve the quality of health services. Community health centers must provide quality health services according to standards. To find out the implementation of the achievements of the community health centers in West Java Province in measuring, reporting, and achieving the national indicators of quality in the community health centers as an effort to maintain and improve service quality. The method used is a descriptive method with secondary data analysis from the national indicators of the quality report on the Mutufasyankes.kemenkes.go.id application, the data is presented in the form of a frequency distribution. The National Quality Indicator Report for 2022 is higher than in 2021, there are 1057 (97%) Community Health Centers that have reported INM, the district/city with the lowest achievement, namely Kab. Ciamis 60%, Banjar City 69%, and Bekasi City 70%, 3 indicators have not reached the target in all districts/cities, namely compliance with the use of PPE, compliance with patient identification, and successful treatment of TB patients for all drug-sensitive cases (SO). There are still districts/cities in West Java province that are not yet compliant with reporting INM, and there are still INM achievements that have not reached the target, it is necessary to optimize the monitoring and evaluation of INM reporting activities by the district/city Health Office.